Amphiphilic invertible polyesters as reducing and stabilizing agents in the formation of metal nanoparticles - Kohut, Ananiy; Voronov, Andriy; Samaryk, Volodymyr; Peukert, Wolfgang (Macromolecular Rapid Communications, 2007)
Metal nanoparticles of various size and shape are prepared by the reduction of metal precursors in polymer micellar architectures (nanoreactors). The nanoreactors are developed from the amphiphilic invertible polyesters solved over a wide concentration range in solvents that strongly differ in polarity. In a non-polar medium, the micelle core contains hydrophilic [poly(ethylene oxide)] fragments, which acts as a reducing agent of metal ions. Nanoparticle stabilization occurs because of the presence of hydrophobic (polymethylene) fragments outside of the micelle structure. The size and shape of the nanoreactors may be altered by the polyester composition and molecular weight as well as by the solvent polarity and concentration of the amphiphilic polyester.
Keywords: amphiphilic polymers; invertibility; metals; nanoparticles; nanoreactors; synthesis